2018
DOI: 10.1002/ase.1803
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Lecture in the Dissection Hall: Transforming Passive Lecture into a Dynamic Learning Experience

Abstract: Traditionally, cadaver dissection and didactic lectures have formed the mainstay of teaching gross anatomy, but, apathy of the learners toward didactic lectures and reduction in the time allotted for teaching anatomy have necessitated adoption of interactive teaching methods that require lesser student contact time. In this study, for two consecutive years, first-year medical students were taught selected gross anatomy topics using Interactive Lecture in the Dissection Hall (ILDH). Instead of discarding the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Even today, the didactic style of teaching forms the basis of learning. Attempts to modernise anatomy are still in their infancy, and recent studies have shown there to be benefit in the use of interactive lecture-based dissection halls [ 23 ] and virtual reality in cardiac anatomy teaching [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even today, the didactic style of teaching forms the basis of learning. Attempts to modernise anatomy are still in their infancy, and recent studies have shown there to be benefit in the use of interactive lecture-based dissection halls [ 23 ] and virtual reality in cardiac anatomy teaching [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire with questions about the TMJ was used to analyse the students' knowledge with respect to this content. This was used because it is a simple resource that is available and easy to administer for the purpose of evaluating performance, with scores ranging from 0 to 10 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…The education of anatomical sciences has gradually shifted from traditional teacher-focused to student-centered methods with less contact time (Chimmalgi, 2019). Advocates for shifting medical education from didactic to interactive lectures claim that interactive lectures are effective in increasing students' attention, knowledge retention, and engagement (Chilwant, 2012).…”
Section: Introductionmentioning
confidence: 99%